Using artificial intelligence in trademark registration in light of the UAE trademark Law - Hassan Al-Tawalbeh, Muayad (Edelweiss Applied Science and Technology, 2024)
When a commercial project is established to produce certain goods or services of high quality to compete and attract consumers, the project owner must adopt a trademark for the good, service or product in order to distinguish what he does from other competing services, goods and production. This requires registering the trademark with the relevant institutions in the country of registration, which requires procedures, requirements and attachments to be submitted. Then comes the role of those institutions in examining the submitted application in accordance with the law in force in the country of registration. Hence, we are discussing the special procedures for registration in the United Arab Emirates, which is one of the most advanced countries in government procedures. We are proposing the idea of introducing artificial intelligence software into the examination and judgment process to speed up the registration process for fear of it being registered by another person in another country that has an agreement with the UAE. Therefore, ownership of the trademark will be for the first to register.